RADT-12. DISEASE CHARACTERISTICS IN ACUTE SEIZURE FOLLOWING RADIOTHERAPY FOR BRAIN METASTASES. (9th November 2020) - Levin-Epstein, Rebecca; Tenn, Stephen; Ruan, Dan; Lahlaf, Safiya; Chu, Brian; Lee, Seung; Steinberg, Michael; Yang, Isaac; Pouratian, Nader; Kim, Won; Hegde, John; Kaprealian, Tania
Abstract: INTRODUCTION: Acute seizure following radiotherapy (RT) for brain metastases is an infrequent but significant adverse event that has not been well-described. Prophylactic antiepileptic drug (AED) or steroid therapy is not recommended for asymptomatic lesions. However, there is minimal data incorporating individualized factors into acute seizure risk-assessment with respect to RT. METHODS: We retrospectively examined patients treated for brain metastases with any RT modality from 2013-2020 who experienced acute post-treatment seizure, which we defined as within 4 weeks post-RT. RESULTS: Twenty patients experienced acute seizure at median 2 days post-treatment (range 0-27); 15 (75%) within 7 days and 7 (35%) on day 0 (radiosurgery date or during fractionated RT). Seizures occurred after radiosurgery (n=9, 45%), fractionated stereotactic RT (n=3, 15%), whole-brain RT (n=5, 25%), and post-operative RT (n=3, 15%). All RT encompassed at least one supratentorial lesion; 11 (55%) had >1 lesion treated. Median lesion size was 23mm (range 7-51mm). Moderate-to-severe perilesional edema was present in 12 (60%) and hemorrhage in 8 (40%) cases. Seizures occurred despite AED therapy in 8 (40%) overall; 5/8 (63%) were hemorrhagic and 7/8 (88%) had moderate-to-severe edema. Nine (45%) patients receiving steroids developed seizures. Primary pathologies were: melanoma (5), non-small cell lung (5), renal cell carcinoma (4), breast (3), colon (1), Merkel cell (1), and thyroid (1). Patients with melanoma who developed acute seizure had mainly non-hemorrhagic (80%), small lesions (median 9mm), not receiving AED (0%) or steroid (20%) therapy. CONCLUSIONS: In acute post-RT seizure, lesions were predominantly supratentorial, >23mm, and had moderate-to-severe edema. Breakthrough seizures were common in edematous and/or hemorrhagic lesions. However, acute seizure also occurred with smaller, non-hemorrhagic melanoma lesions not receiving AED therapy. A larger series is needed to further evaluate these identified characteristics in acute seizure, and whether prophylactic therapy may be appropriate.